(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The importance of learning English is growing in modern society. This language is not only a means of international relations, but also provides many opportunities necessary for success in personal and professional life. Through knowledge of the English language, people expand their range of knowledge, get acquainted with new cultures and have the opportunity to actively participate in the global arena.